Γ‐H2AX formation in the urinary bladder of rats treated with two norharman derivatives obtained from o‐toluidine and aniline. Issue 4 (16th November 2017) - Toyoda, T.; Totsuka, Y.; Matsushita, K.; Morikawa, T.; Miyoshi, N.; Wakabayashi, K.; Ogawa, K.
Abstract: Aminomethylphenylnorharman (AMPNH) and aminophenylnorharman (APNH) are mutagenic norharman derivatives obtained from o ‐toluidine and aniline, respectively. APNH is carcinogenic to the urinary bladder of rats and present in urine samples of healthy volunteers, indicating that norharman derivatives may be associated with cancer development in the urinary bladder of humans. To evaluate the possible role of AMPNH and APNH in bladder carcinogenesis, we examined the formation of γ‐H2AX, a DNA damage response marker, in the urinary bladder of rats. Seven‐week‐old male F344 rats were treated with 400 ppm AMPNH or 40 ppm APNH in the diet for 4 weeks. Animals were killed at the end of administration or after 2 weeks of recovery, and immunohistochemistry for γ‐H2AX and Ki67, a cell proliferation marker, was performed. At week 4, γ‐H2AX formation in bladder epithelial cells was significantly increased by APNH treatment as compared with that in controls. AMPNH also induced upregulation of γ‐H2AX formation, although there was no statistical significance. After the recovery period, γ‐H2AX‐positive cells were reduced but remained significantly higher in AMPNH and APNH groups than in the control group. Ki67‐positive cells were significantly increased by AMPNH and APNH at week 4 and reduced to the same level as the control after 2 weeks of recovery. Expression of KRT14, a bladder stem cell marker, was also increased in the basal layer by the two norharman derivatives. Thus, AMPNH and APNH showed in vivo genotoxicity in the bladder epithelium of rats, and APNH may be a potent causative agent of bladder carcinogenesis. Abstract : To evaluate the role of norharman derivatives in bladder carcinogenesis, we examined γ‐H2AX formation in the urinary bladder of male rats treated with aminomethylphenylnorharman (AMPNH) or aminophenylnorharman (APNH) for 4 weeks. γ‐H2AX formation in the urothelium was increased in both groups at week 4. After 2 weeks of recovery, γ‐H2AX‐positive cells remained significantly‐high levels in both groups. Thus, AMPNH and APNH showed in vivo genotoxicity in the bladder epithelium, and APNH may be a potent causative agent of bladder carcinogenesis.